Ethnic Conflict in Karachi: Diagnosing and Conflict Resolution - Maria Saifuddin Effendi; Dr. Nazir Hussain (Journal of Political Studies, 2018)
Karachi represents a multi-dimensional intra-state conflict that has claimed thousands of innocent lives due to rampant ethnic, political, sectarian and criminal violence. Gauging the origins and development of the ethnic conflict in Karachi, it seems that the city has seen different patterns of ethnic conflict and violence during the last 70 years of Pakistan‟s independence. This study is dedicated to evaluate and assess different stages of ethnic conflicts in Karachi by applying Conflict Life Cycle Model. The model entails seven stages of conflict formation and management and finally resolution. Though unique, Karachi has passed through almost all stages of the conflict formation but missed the most mature stage of conflict ripeness i.e. Mutually Hurting Stalemate stage, which often encourages conflict actors to seek a way out through negotiation or peace process. This paper suggests a sustainable conflict management and resolution mechanism to the ethnic conflict in Karachi.